Validation of the Antibacterial Efficacy of the Essentail Oils from the Leaves of Parquetina Nigrescens (Asclepiadaceae): Validation of the Antibacterial Efficacy (Journal of Science and Technology, 2025)
Essential oils are complex mixtures of volatile compounds that are extracted from different parts of plants and possess diverse biological activity. In this work, the essential oils of Parquetina nigrescens leaves harvested in Ijebu-Ode, Ogun state, were extracted using hydrodistillation and the oils were analysed with Gas Chromatography Mass Spectrometry (GC-MS). Twenty six (26) different compounds were found in the oil with Caryophyllene (49.38 %) and α-Citral (14.49%), being the most prevalent chemical compounds detected while Endo–Borneol (6.06 %), Citral (5.82 %), 3-Carene (4.18 %), 10-epi- γ-Eudesmol (3.75 %), Selin-6-en-4α-ol (3.76 %), and α-Pinene (2.19 %) were present is smaller quantities and other compounds were only found available in negligible amounts. The oil was screened for its antibacterial activity against K. pneumoniae, E. coli, and S. aureus. In comparison to the standard drug, the oil displayed good activity against the bacteria screened. E. Coli was the most susceptible to the antibacterial effect of the oil, as the best activity was observed against it (22.00±1.26 mm), followed by K. pneumonia (19.00±1.11 mm) and S. aerus (18.00±1.23 mm). This result underscores the relevance of Parquetina nigrescens in traditional medicine practice.